Local Mutual Exclusion for Dynamic, Anonymous, Bounded Memory Message Passing Systems - Daymude, Joshua J.; Richa, Andréa W.; Scheideler, Christian (1st Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2022, March 28-30, 2022, Virtual Conference)

The Market for Belief Systems: A Formal Model of Ideological Choice - Gries, Thomas; Müller, Veronika; Jost, John T. (Psychological Inquiry)
Keywords: General Psychology

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Medienbildung als Radikalisierungsprävention? - Herzig, Bardo (Radikalisierungsnarrative online. Perspektiven und Lehren aus Wissenschaft und Prävention)

Lehren und Lernen mit (digitalen) Medien im Pädagogikunterricht - Herzig, Bardo; Martin, Alexander (Handbuch Pädagogikunterricht)

PLS-Based Structural Equation Modelling: An Alternative Approach to Estimating Complex Relationships Between Unobserved Constructs - Goller, Michael; Hilkenmeier, Frederic (Methods for Researching Professional Learning and Development)

Addressing Methodological Challenges in Research on Professional Learning and Development - Goller, Michael; Kyndt, Eva; Paloniemi, Susanna; Damşa, Crina (Methods for Researching Professional Learning and Development)

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for Researching Professional Learning and Development)

Participant’s Video Annotations as a Database to Measure Professional Development - Steffen, Bianca; Pouta, Maikki (Methods for Researching Professional Learning and Development)

Uncovering Informal Workplace Learning by Using Diaries - Rausch, Andreas; Goller, Michael; Steffen, Bianca (Methods for Researching Professional Learning and Development)

Delphi-Technique as a Method for Research on Professional Learning - Harteis, Christian (Methods for Researching Professional Learning and Development)

Kompetenzerwerb auf der Schulstation: Eine Mixed-Methods-Replikationsstudie - Goller, Michael; Steffen, Bianca; Lau, D. (Professionalisierung der Gesundheitsberufe. Berufliche und hochschulische Bildung im Spiegel aktueller Forschung)

Essays on Industrial Organization and Networks: Retail Bundling, Exclusive Dealing, and Network Disruption - Endres-Fröhlich, Angelika Elfriede

Methods for Researching Professional Learning and Development

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Requirements-Based Composition of Tailored Decision Support Systems - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Human-Centered Software Engineering)
Corporate decision makers have individual requirements for decision support influenced by business goals, regulatory restrictions or access to resources such as data. Ideally, decision makers could quickly create tailored decision support systems (DSS) themselves which optimally address their individual requirements for decision support. Although service-oriented architectures have been proposed for DSS customization, they are primarily targeting trained software developers and cannot immediately be adapted by decision makers or domain experts with little to no software development knowledge. In this paper, we therefore motivate an assisted process-based service composition approach which can be used by non-developers to create tailored DSS. For assistance during service composition, we contribute a meta-model for the formalization of both decision support requirements and functionality of decision support services. Models created according to the meta-model can be used to detect mismatches between a decision maker’s requirements for decision support and services selected in the service composition representing a DSS. Furthermore, the formalizations may even be used for automated service composition given a decision maker’s decision support requirements. We demonstrate the expressiveness of our meta-model in the domain of regional energy distribution network planning.

Amplified steady state bifurcations in feedforward networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (Nonlinearity)
We investigate bifurcations in feedforward coupled cell networks. Feedforward structure (the absence of feedback) can be defined by a partial order on the cells. We use this property to study generic one-parameter steady state bifurcations for such networks. Branching solutions and their asymptotics are described in terms of Taylor coefficients of the internal dynamics. They can be determined via an algorithm that only exploits the network structure. Similar to previous results on feedforward chains, we observe amplifications of the growth rates of steady state branches induced by the feedforward structure. However, contrary to these earlier results, as the interaction scenarios can be more complicated in general feedforward networks, different branching patterns and different amplifications can occur for different regions in the space of Taylor coefficients.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Influence of Screw Design on Fiber Breakage of Glass Fiber Reinforced Polypropylene in the Injection Molding Process - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (37th International Conference of the Polymer Processing Society (PPS))

Characterization of Fiber Dust Resulting from Recycling of Carbon Fiber-Reinforced Thermoplastics (CFRP) and Their Cell Toxicity - Hopp, Matthias; Tölle, Lisa; Monsé, C.; Rosenkranz, N.; Haibel, N.; Walter, D.; Bünger, J.; Westphal, G. (Journal of Material Science and Chemical Engineering)

Multimaterial Injection Moulding of Thermosets and Elastomers - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (ScienceBG)